An evaluation of occupational safety culture in woodworking and furniture industries: A case study in Gümüşhane province - Mehmet Yaşar; Muhammed Said Fidan; Şekip Şadiye Yaşar; Osman Komut (Turkish Journal of Forestry, 2023)
The furniture industry sector in Turkey provides an important employment area throughout the country with its small and medium-sized business structure. On the other hand, the sector is among the fields of activity in which the negativities in terms of occupational health and safety are experienced. In this context, a survey based on face-to-face interviews was conducted with a total of 54 employees. In the study, the situation of the workplaces and the opinions of the employees on the subject were tried to be determined with the propositions prepared in a 5-point Likert scale. In the study, besides the proportional comparisons on the data obtained, the Mann Witney U test was used in the analysis of occupational safety factors according to the variable of exposure to work accident. According to the findings, 67% of the participating enterprises have an operating period of less than 5 years. In addition, it has been determined that there are deficiencies in the use of personal protective equipment and periodic health examinations. While the occupational accident exposure of the participants was determined as 72%, it was understood that the hands and fingers were predominantly injured limbs. On the other hand, it has been determined that occupational accident exposure creates statistically significant differences (p<0.05) regarding the views on occupational safety factors. As a result, it can be said that the culture of occupational health and safety is not sufficiently developed in small and medium-sized woodworking and furniture enterprises.